Ethics and quality in blood services - García Crispieri, María del Carmen (Acta Bioethica, 2011)
The increasing link among ethics-science-technology-quality-society, especially in the last four decades, has had great implications in transfusion medicine. In present study, relations among ethics, bioethics and quality aspects and their application in the field of transfusion medicine are analyzed, as a necessary consequence of principles that influence physical, psychological and spiritual lives of persons.